2008
DOI: 10.1086/533545
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Transmission of Multidrug-ResistantAcinetobacter baumanniiClonal Strains Causing Episodes of Sepsis in a Trauma Intensive Care Unit

Abstract: The extensive dissemination of imipenem-resistant A. baumannii clonal strains causing episodes of bacteremia and/or sepsis resulted from modes of transmission via multiple contaminated surfaces and objects and transiently colonized HCWs' hands. Closure of the ICU and its meticulous environmental decontamination led to the successful control of the outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 28 publications
(23 reference statements)
1
47
0
8
Order By: Relevance
“…There have been reports of contaminated units for which complete closure was required to control the outbreaks (16,17). In contrast, a recent study reported that closure of contaminated units was not crucial, as strict contact precautions to control an A. baumannii outbreak were sufficient (18).…”
mentioning
confidence: 99%
“…There have been reports of contaminated units for which complete closure was required to control the outbreaks (16,17). In contrast, a recent study reported that closure of contaminated units was not crucial, as strict contact precautions to control an A. baumannii outbreak were sufficient (18).…”
mentioning
confidence: 99%
“…Multi drug resistant A. baumannii is a common challenge in treatment of hospital infections in many countries, including America, Italy, Korea, Greece, Belgium and Iraq (9)(10)(11)(12)(13)(14).The spread on antibiotic resistance among AcJundishapur J Microbiol. 2017; 10(11):e59370.…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned properties of these species and the emerging antibiotic resistance for A. baumannii, could be related to biofilm formation. Outer membrane proteins (OMPs) are the plentiful surface proteins of this organism cause of nosocomial infections (6,(9)(10)(11)(12)(13)(14)(15). The most important way for restriction of infectious diseases is vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…It has been increasingly implicated in colonization and infection of patient admitted in hospitals [12]. Due to it fluid genome, this bacterium has the ability to attain rapid resistance to most of the commonly employed antimicrobials.…”
Section: Discussionmentioning
confidence: 99%